The North Atlantic Port Differentials - Harbeson, R. W. (Quarterly Journal of Economics, 1932)
I. The historical background, 644. — The present adjustment, 646. — II. Summary of arguments for and against the existing system, 647. — III. The Fink Report, 651. — The Thurman Commission, 652. — Early cases before the Interstate Commerce Commission, 653. — Later cases, 655. — IV. Advantages of distance, 657. — Terminal costs, 658. — Ocean rates, 660. — V. Probable results of equalizing rail rates, 662. — Basis of New York's dominance, 664. — Boston's difficulties, 667. — Conclusion: the differentials a special case of equalization in rate-making, 669.